Morphology and tensile properties of polypropylene-multiwalled carbon nanotubes composite fibers - Tawat Soitong (2018)
In this work, we analyzed tensile properties of polypropylene-multiwalled carbon nonotubes composite fibers. The multiwalled carbon nanotubes (MWCNTS) were used in different contents of 0, 1, 2, 3, 4, and 5 wt %. Dispersing agents were used to disperse MWCNTs in polypropylene matrix. After the dispersing agent was removed, the mixture was melt mixed. The fibers were spun by a home-made melt spinning equipment and stretching was done at a draw ratio of 7.5. By using 1-5 wt % of MWCNTs, the modulus of composite fibers increased by 69-84% and tensile strength increased about 39% when compared with the virgin polypropylene fibers. In addition, the MWCNTs dispersion in the matrix was monitored by scanning electron microscopy and transmission electron microscopy. © 2010 Wiley Periodicals, Inc.